2019
DOI: 10.3168/jds.2019-16321
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction improved feed efficiency of inefficient lactating cows

Abstract: The aim of this study was to reduce voluntary dry matter intake (DMI) to increase feeding efficiency of preclassified inefficient (INE) dairy cows through restricted feeding. We studied the effects of dietary restriction on eating behavior, milk and energy-corrected milk (ECM) production, in vivo digestibility, energy balance, and measures of feed efficiency [residual feed intake (RFI) and ECM/DMI]. Before the experiment, 12 pairs of cows were classified as INE. The 2 dietary treatments consisted of ad libitum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
3
6
0
2
Order By: Relevance
“…The vast majority of phenotypic correlations between feeding behavior traits and feed efficiency traits followed the same direction as genetic correlations for the corresponding traits, but with lower magnitude. Despite being limited in number, studies in dairy cattle nutrition have reported differences between feeding behavior in groups of animals classified as high or low RFI (Williams et al, 2011;Ben Meir et al, 2019). In support of our data, slower feeding rate and shorter daily feeding duration have been reported in efficient animals (Green et al, 2013;Xi et al, 2016).…”
Section: Genetic and Phenotypic Correlations Between Feeding Behavior...supporting
confidence: 89%
“…The vast majority of phenotypic correlations between feeding behavior traits and feed efficiency traits followed the same direction as genetic correlations for the corresponding traits, but with lower magnitude. Despite being limited in number, studies in dairy cattle nutrition have reported differences between feeding behavior in groups of animals classified as high or low RFI (Williams et al, 2011;Ben Meir et al, 2019). In support of our data, slower feeding rate and shorter daily feeding duration have been reported in efficient animals (Green et al, 2013;Xi et al, 2016).…”
Section: Genetic and Phenotypic Correlations Between Feeding Behavior...supporting
confidence: 89%
“…Few production differences were observed once cows adapted to diet feeding regimens. However, consistent with other recent studies (Ben Meir et al, 2019), ECM feed efficiency was slightly improved in cows that had access to feed 19 versus 24 h/d due to slightly lower DMI.…”
supporting
confidence: 92%
“…However, this hay intake was not equal to the reduction in TMR intake, likely due to feed palatability or preference for the TMR over the hay alone. Restricted DMI has also been shown to improve feed efficiency in lactating cows (Ben Meir et al, 2019) and may represent an alternative feeding strategy in some situations.…”
Section: Limiting Total Mixed Ration Availability Alters Eating and Rumination Patterns Of Lactating Dairy Cowsmentioning
confidence: 99%
“…Additionally, interactions exist between nutrient intake and FB, which could be further manipulated. For example, researchers have attempted to increase feed efficiency through feed restriction, which reduced eating time, meal frequency, and bin visit frequency (Ben Meir et al, 2019). If a temporal relationship exists between FB and RFI, then perhaps inefficient cows can be managed in a manner to alter daily and temporal FB patterns and increase efficiency.…”
Section: Introductionmentioning
confidence: 99%